Quality of Work Life dan Burnout terhadap Kinerja Paramedis: Mediasi Kepuasan Kerja di Era Pandemi - Priyono, Achmad Agus; Saraswati, Ety (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The Covid-19 pandemic that hit the world and claimed millions of lives has resulted in an increase in the excessive workload on paramedics. This condition places paramedics at risk of exposure to the Covid-19 virus, as well as increases the risk of burnout syndrome or mental fatigue.The research aims to analyze the quality of work life (QWL) and burnout on the performance of paramedics with job satisfaction as a mediating variable. The research was conducted on paramedics at Grati Hospital, Pasuruan Regency, using a saturated sampling technique. Data analysis used SEM-PLS with SmartPLS 3.2.9 software. The results showed that paramedics' job satisfaction and QWL had a significant positive effect, while burnout had a significant negative effect on paramedics' performance. Meanwhile QWL proved to have a significant positive effect on paramedics' job satisfaction. The results of the indirect effect prove that paramedics' job satisfaction is able to mediate the relationship between QWL and paramedics' performance.